Hello,
please if you can have a look through my workings.
integr[(e^(4x))cosh5x]dx = (1/5)[(e^(4x))sinh5x] - (4/25)integr[(e^(4x))cosh5x] = (1/5)[(e^(4x))sinh5x] - (4/25)(e^(4x))cosh5x + (16/25)integr[(e^(4x))cosh5x)] => (9/25)integr[(e^(4x))cosh5x]dx = [(1/25)(e^(4x)](5sinh5x - 4cosh5x) = [(1/25)[(e^(9x))-9(e^(-x))] => integr[(e^(4x))cosh5x]dx = (1/9)(e^(9x))-(e^(-x))] . My book though says it equals
(1/18)(e^(9x))-(1/2)(e^(-x))]
thanks for any help
Wow! Take a look...
http://www.mathhelpforum.com/math-he...-tutorial.html